Selective and mild oxidation of α-hydroxyl groups in lignin by 2-iodoxybenzoic acid - Jiang, Fei; Dong, Zhiming; Lou, Xiaoli; Zhang, Zhuonan; Shuai, Li; Zhao, Chengke (Frontiers in Bioengineering and Biotechnology, 2025)
Secondary benzyl alcohols (α-OH) in lignin β-O-4 linkages are reactive sites that can trigger undesirable condensation reactions during lignin valorization processes. The selective oxidation of α-OH groups can effectively inhibit lignin condensation reactions, thereby promoting lignin depolymerization. Meanwhile, this approach increases the functionalities, which is beneficial for the design of lignin-derived functional materials. In this study, we report a chemoselective oxidation method using 2-iodoxybenzoic acid (IBX) to selectively convert α-OH groups into ketones. The reaction proceeds under ambient conditions with green DMSO as the sole solvent. Oxidation of β–O–4 model compound (veratrylglycerol-β-guaiacyl ether, VG) revealed exceptional selectivity of this oxidation process, achieving 92% substrate conversion with 90% yield of the corresponding α-ketone product after 48 h. When applied to cellulolytic enzyme lignin, this protocol significantly increased the α-ketone content from 1.2% to 20.5% (relative to total interunit linkages), as identified and quantified by 2D HSQC NMR. The straightforward α-OH oxidation protocol demonstrates significant potential for precise lignin structure modification and rational design of lignin-derived functional materials in sustainable polymer systems.